Fixed point theorems for two pairs of mappings satisfying a new type of common limit range property in G_p metric spaces - Popa, Valeriu; Patriciu, Alina-Mihaela (Annales Mathematicae Silesianae, 2018)
The purpose of this paper is to prove a general fixed point theorem for mappings involving almost altering distances and satisfying a new type of common limit range property in Gp metric spaces. In the last part of the paper, some fixed point results for mappings satisfying contractive conditions of integral type and for '-contractive mappings are obtained.